2009
DOI: 10.1590/s0034-89102009005000020
|View full text |Cite
|
Sign up to set email alerts
|

Fidedignidade de rótulos de alimentos comercializados no município de São Paulo, SP

Abstract: OBJECTIVE:To assess reliability of information about nutritional facts stated on labels of industrialized foods. METHODS:A total of 153 industrialized foods, usually consumed by children and adolescents and marketed in the city of São Paulo, Southeastern Brazil, between 2001 and 2005, were analyzed. Nutrient contents stated on labels were compared to the results obtained from offi cial (physical-chemical) analytical methods, considering the 20% variability tolerated by the current legislation to approve or rej… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
25

Year Published

2011
2011
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 7 publications
1
6
0
25
Order By: Relevance
“…In a study on sandwich and wafer biscuits, the percentage of non-compliant samples with the 20% tolerance limit of RDC 360 (BRASIL, 2003) was 36% and 6%, respectively (LOBANCO et al, 2009). Lee et al (2008) found a value of 2.52 g/100 g of total fiber in cream crackers, which is similar to the value found in the present study for cream cracker brand A.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…In a study on sandwich and wafer biscuits, the percentage of non-compliant samples with the 20% tolerance limit of RDC 360 (BRASIL, 2003) was 36% and 6%, respectively (LOBANCO et al, 2009). Lee et al (2008) found a value of 2.52 g/100 g of total fiber in cream crackers, which is similar to the value found in the present study for cream cracker brand A.…”
Section: Discussionsupporting
confidence: 85%
“…This large difference may be related to the inevitable varying composition of the raw materials, the different methods of analysis, and also because, sometimes, information in the FCDB of other countries' can be used instead of that from the food's country of origin, which would be more accurate. Lobanco et al (2009), studying Brazilian food products, found that all of the sandwich and wafer biscuit samples evaluated were compliant with the legislation previously mentioned; Kus et al (2011) found the same results in samples of infant formulas.…”
Section: Chemical Compositionmentioning
confidence: 58%
See 2 more Smart Citations
“…These labels in Brazil did not provide information concerning monounsaturated or polyunsatured fat; therefore, their intake may have been underestimated, particularly for the children who consumed large amounts of industrualized foods (high percentage of saturated fat). A recent Brazilian study [43] showed nutritional information inadequacy on the labels of snacks (saturated fat, fiber and sodium) and cookies (saturated fats); these foods were largely consumed by the children that participated of this study. Another possible limitation related to dietary intake was the underreporting, that is more frequent in overweight children compared to eutrophic ones [21].…”
Section: Discussionmentioning
confidence: 99%